Phosphate modified positive electrode material as well as preparation method and application thereof

By constructing a phosphate cladding layer on the surface of the positive electrode material of lithium-ion batteries, the problem of insufficient cladding uniformity and controllability in the prior art is solved, the structural and cycle stability of the positive electrode material is improved, and the electrochemical performance of the battery is significantly improved.

CN119725413AActive Publication Date: 2025-03-28INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311263388.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The prior art has problems of difficulty in ensuring uniformity and controllability in the surface phosphate coating of the positive electrode material of lithium-ion batteries, which makes it difficult to establish an accurate connection between the coating structure and performance.

Method used

By dissolving the metal salt and the phosphorus source in deionized water, a mixed solution is formed, and the coated substrate material is dispersed in this solution, a countersolvent is added and the reaction is stirred, and finally a phosphate modified positive electrode material is obtained by calcination.

Benefits of technology

The phosphate cladding layer is uniformly and controllable on the surface of the positive electrode material of lithium-ion batteries, which improves the structural stability and cycle stability of the positive electrode material, and significantly improves the electrochemical cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725413A_ABST
    Figure CN119725413A_ABST
Patent Text Reader

Abstract

The invention provides a phosphate modified positive electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: 1) dissolving a metal salt and a phosphorus source in deionized water, and reacting to form a mixed solution; 2) dispersing a coated substrate material in the mixed solution formed in the step 1) to obtain a turbid solution; (3) carrying out stirring reaction on an anti-solvent and the turbid solution formed in the step (2), centrifuging, washing and drying to obtain substrate powder coated with metal phosphorus-containing species; and 4) calcining the substrate powder formed in the step 3) to obtain the phosphate modified positive electrode material. The metal phosphate modified positive electrode material particles obtained by the invention can be used for realizing a stable positive electrode material of a high-specific-energy energy storage lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical and energy materials, and specifically relates to a phosphate-modified positive electrode material and a preparation method and application thereof. Background Art

[0002] Surface coating has important application value in the fields of materials and chemistry. It can controllably construct uniform modified species on the surface of different substrate materials, which can give the materials new properties and uses. Especially in the field of lithium-ion batteries, it is well known that the positive electrode materials of lithium-ion batteries are very likely to react with flammable organic electrolytes during the charging and discharging process, resulting in serious damage to the material interface structure and an increase in the battery interface impedance, which sharply reduces the battery capacity and cycle life. As a modification strategy, surface coating can effectively block the direct contact between the positive electrode active material and the organic electrolyte, protect the positive electrode material from the erosion of the electrolyte, and thus improve the structural stability and cycle stability of the positive electrode material.

[0003] Metal phosphate is a coating species that has attracted much attention. It has excellent structural stability and has obvious advantages in stabilizing the interface structure of battery positive electrode materials. At present, the coating methods based on phosphate are very limited, mainly including solid-phase ball milling mixing, liquid-phase evaporation of solvents, atomic layer deposition and other methods. Recent invention patents CN111916702B and others use solid-phase mixing combined with calcination to obtain phosphate-coated lithium-ion battery positive electrode materials. Invention patents CN110190254A and others use a method of directly mixing a phosphoric acid source with an electrode material and evaporating to form a lithium phosphate-coated ternary positive electrode material, which all show improved battery cycle performance. However, such high-energy consumption methods such as solid-phase ball milling mixing and liquid-phase evaporation of solvents cannot guarantee the uniformity and controllable distribution of the coating species, so that an accurate connection cannot be established between the final coating structure and performance. Although atomic layer deposition and other methods can achieve uniform coating of surface phosphate species, they cannot be scaled up and applied on a large scale due to their expensive equipment and complicated operating procedures. Therefore, there is an urgent need to develop new methods that are low-cost, low-energy, and easy to scale up industrially to achieve uniform surface phosphate coating. Summary of the invention

[0004] The purpose of the present invention is to provide a phosphate-modified positive electrode material and a preparation method and application thereof.

[0005] To solve the above problems, the present invention provides the following technical solutions:

[0006] A method for preparing a phosphate-modified positive electrode material, the preparation method comprising:

[0007] 1) dissolving a metal salt and a phosphorus source in deionized water, reacting to form a mixed solution;

[0008] 2) dispersing the coated substrate material in the mixed solution formed in step 1) to obtain a turbid solution;

[0009] 3) stirring the anti-solvent and the turbid solution formed in step 2) to react, centrifuging, washing, and drying to obtain a base powder coated with a metal phosphorus-containing species;

[0010] 4) The base powder formed in step 3) is calcined to obtain a phosphate-modified positive electrode material.

[0011] According to an embodiment of the present invention, the metal salt is selected from one or more of chlorides, sulfates, nitrates, acetates and alkoxides of metal elements, preferably sulfates of metal elements. Preferably, the metal element is selected from at least one of aluminum, nickel, manganese, cobalt, iron, copper, zinc, titanium, zirconium, niobium, tantalum and magnesium, preferably aluminum, nickel, manganese and cobalt.

[0012] According to an embodiment of the present invention, in the mixed solution of step 1), the concentration of the metal salt is 0.001 to 1 mol / L.

[0013] According to an embodiment of the present invention, the phosphorus source is selected from one or more of the corresponding ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, and potassium phosphate, preferably ammonium dihydrogen phosphate.

[0014] According to an embodiment of the present invention, in the mixed solution of step 1), the concentration of the phosphorus source is 0.001 to 1 mol / L.

[0015] According to an embodiment of the present invention, in the mixed solution of step 1), the reaction conditions for forming the mixed solution include: the reaction temperature is room temperature to 60°C, preferably room temperature; the reaction time is 1h-72h, preferably 12h.

[0016] According to an embodiment of the present invention, in the mixed solution of step 1), the molar ratio of the metal salt to the phosphorus source is 0.001-1:0.001-1.

[0017] According to an embodiment of the present invention, the coating substrate material is selected from at least one of metal materials, non-metal materials, oxides, sulfides, carbides, nitrides, phosphides, lithium salt positive electrode materials, sodium salt positive electrode materials, potassium salt positive electrode materials, and organic particles.

[0018] According to an embodiment of the present invention, the metal in the coating substrate material is selected from at least one of gold, silver, ruthenium, rhodium, palladium, platinum, germanium, tin, antimony and alloys thereof.

[0019] According to an embodiment of the present invention, the non-metal in the coating substrate material is selected from at least one of carbon, silicon, sulfur, phosphorus and selenium.

[0020] According to an embodiment of the present invention, the oxide in the coated substrate material is selected from at least one of silicon dioxide, titanium dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium oxide, manganese dioxide, manganese tetraoxide, iron oxide, iron oxide, cobalt oxide, nickel oxide, vanadium pentoxide, zirconium oxide, molybdenum oxide, indium tin oxide, tin oxide, and lithium lanthanum zirconium oxide.

[0021] According to an embodiment of the present invention, the sulfide in the coated substrate material is selected from at least one of zinc sulfide, tungsten sulfide, bismuth sulfide, titanium disulfide, iron sulfide, cobalt sulfide, nickel sulfide, molybdenum sulfide, tin sulfide and antimony sulfide.

[0022] According to an embodiment of the present invention, the carbide in the coating substrate material is selected from at least one of silicon carbide, titanium carbide, calcium carbide, vanadium carbide, chromium carbide, tantalum carbide, tungsten carbide and boron carbide.

[0023] According to an embodiment of the present invention, the nitride in the coating substrate material is selected from at least one of boron nitride, gallium nitride, silicon nitride, titanium nitride, vanadium nitride, niobium nitride, tungsten nitride and phosphorus nitride.

[0024] According to an embodiment of the present invention, the phosphide in the coated substrate material is selected from at least one of iron phosphide, cobalt phosphide, nickel phosphide, titanium phosphide, molybdenum phosphide and tin phosphide.

[0025] According to an embodiment of the present invention, the lithium salt positive electrode material in the coated substrate material includes but is not limited to at least one of lithium titanate, lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium-rich nickel cobalt manganese oxide, lithium titanium phosphate, lithium titanium aluminum phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and lithium manganese cobalt phosphate.

[0026] According to an embodiment of the present invention, the sodium salt positive electrode material in the coated substrate material includes but is not limited to at least one of oxide sodium salt positive electrode materials, polyanion sodium salt positive electrode materials, Prussian blue sodium salt positive electrode materials, fluoride sodium salt positive electrode materials, and organic compound sodium salt positive electrode materials.

[0027] According to an embodiment of the present invention, the potassium salt positive electrode material in the coated substrate material includes but is not limited to at least one of Prussian blue-based potassium salt positive electrode materials, layered oxide-based potassium salt positive electrode materials, polyanion-based potassium salt positive electrode materials, and organic material-based potassium salt positive electrode materials.

[0028] According to an embodiment of the present invention, the organic particles in the coating substrate material are selected from at least one of phenolic resin, urea-formaldehyde resin, melamine resin, polystyrene, polydopamine, and polyvinyl pyrrolidone.

[0029] According to an embodiment of the present invention, in step 2), the turbid liquid is also required to be obtained by ultrasonic dispersion and / or stirring.

[0030] According to an embodiment of the present invention, in the turbid liquid of step 2), the concentration of the coated substrate is 0.001 to 1000 g / L.

[0031] According to an embodiment of the present invention, the anti-solvent includes but is not limited to at least one of methanol, ethanol, propanol, butanol, pentanol, hexanol, acetone, butanone, furfural, acetonitrile, and dioxane, preferably ethanol.

[0032] According to an embodiment of the present invention, in step 3), the volume ratio of the turbid liquid to the anti-solvent is 1-30:30-100, for example, 15:45.

[0033] According to an embodiment of the present invention, the method of mixing the turbid liquid with the anti-solvent comprises: directly pouring the turbid liquid, slowly dripping it, and controlling the dripping rate by a peristaltic pump to drip it into the anti-solvent; or, directly pouring the anti-solvent, slowly dripping it, and controlling the dripping rate by a peristaltic pump to drip it into the turbid liquid.

[0034] According to an embodiment of the present invention, the temperature at which the turbid solution and the anti-solvent are stirred is room temperature to 80° C., preferably room temperature.

[0035] According to an embodiment of the present invention, the rotation speed of stirring the turbid liquid and the anti-solvent is between 100 r / min and 1000 r / min, preferably 600 r / min.

[0036] According to an embodiment of the present invention, the stirring reaction time is 5 to 240 minutes.

[0037] According to an embodiment of the present invention, the calcination atmosphere is at least one of oxygen, air, nitrogen and argon.

[0038] According to an embodiment of the present invention, the calcination conditions include: a calcination temperature of 300 to 900° C. and a calcination time of 1 to 10 hours.

[0039] The present invention also provides a phosphate-modified positive electrode material, and the phosphate-modified positive electrode material is prepared by the above-mentioned preparation method.

[0040] According to an embodiment of the present invention, the phosphate-modified positive electrode material is a particle having a core-shell structure.

[0041] According to an embodiment of the present invention, the phosphate-modified positive electrode material comprises a nano-coating shell layer and a coating substrate material, wherein the nano-coating shell layer is modified on the surface of the coating substrate material; the coating substrate material has the meaning as described above; and the nano-coating shell layer comprises phosphate. Preferably, the nano-coating shell layer partially coats or fully coats the surface of the coating substrate material, preferably fully coats. Further, the nano-coating shell layer is continuously and uniformly distributed on the surface of the coating substrate material.

[0042] According to an embodiment of the present invention, the nano-coating shell layer includes phosphates of metal elements, such as but not limited to at least one of aluminum phosphate, nickel phosphate, manganese phosphate, cobalt phosphate, iron phosphate, copper phosphate, zinc phosphate, titanium phosphate, zirconium phosphate, niobium phosphate, tantalum phosphate, and magnesium phosphate, preferably aluminum phosphate, nickel phosphate, manganese phosphate, and cobalt phosphate.

[0043] According to an embodiment of the present invention, the thickness of the nano-coating shell layer is 0 nm to 500 nm, for example, 1 nm, 1.5 nm, 5 nm, 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, or 400 nm.

[0044] The present invention also provides the use of the phosphate-modified positive electrode material in an energy storage battery.

[0045] It is used to construct high specific energy storage batteries.

[0046] Beneficial effects:

[0047] The method of the invention can be used as a modification strategy for constructing a nano-scale phosphate coating layer on the interface of the positive electrode material of a lithium ion battery or a lithium battery.

[0048] The obtained metal phosphate coated particles with a core-shell structure can be used as a substrate for controllably and uniformly coating the positive electrode material of a lithium ion battery or a lithium battery.

[0049] The metal phosphate-modified positive electrode material particles obtained by the present invention can be used to realize the positive electrode material of a stable high-energy-density energy storage lithium-ion battery.

[0050] The present invention provides a positive electrode material modified with surface phosphate, and a preparation method and application thereof, wherein metal salts and ammonium dihydrogen phosphate are fully dissolved and reacted in an aqueous solution, and an anti-solvent is gradually introduced into the mixed system, so that the metal phosphorus-containing substance of the reaction product slowly precipitates and deposits on the surface of the existing substrate seed, and gradually grows on the surface to form a continuous and uniform coating layer. The reaction rate of species growth can be regulated by controlling the concentration of metal salts and phosphorus sources, the amount of anti-solvents, the substrate concentration, the feeding and mixing method, etc., thereby ensuring the uniform and controllable deposition of the coated species, and the thickness of the interface coating layer can also be conveniently regulated. The method adopts a mild liquid phase method to introduce a metal phosphate nanolayer on the surface of different substrates, has low cost and strong controllability, and the formed coated material has a very broad application prospect.

[0051] This invention provides a new method that is easy to operate, efficient and green, and is used to construct a metal phosphate coating on the surface of a substrate. This method uses a mild liquid phase strategy to regulate the controllable deposition of metal phosphorus-containing species on the surface of the substrate. Metal salts and phosphorus sources are fully reacted in water to form a clear solution. The interaction between the reaction products and the new solvent is utilized to achieve uniform and continuous coating of metal phosphorus-containing species on the surface of the substrate by regulating the feeding mixing method, feeding speed, reactant concentration, pH value, etc. After heat treatment, uniform metal phosphate can be constructed on the surface of the substrate. This method is suitable for different substrate materials, especially for various positive electrode materials of lithium-ion batteries. It can design and form a uniform phosphate nano-protective layer on its surface to inhibit battery interface side reactions and significantly improve the electrochemical cycle stability of the battery. This method provides a control strategy suitable for large-scale processing of modified lithium-ion battery positive electrode materials, and has a very broad application value.

[0052] The present invention utilizes the interaction between metal salts, phosphorus sources, water, and anti-solvents to construct a coating layer of metal phosphorus species at the interface of the positive electrode material of the lithium-ion battery, and converts it into a metal phosphate interface modification layer by calcination. This strategy can effectively block the direct contact between the positive electrode active material and the electrolyte, greatly reducing the interfacial impedance of the battery during the cycle, thereby improving the structural stability of the positive electrode material during the electrochemical cycle, especially at a high cut-off voltage. By changing the amount of the positive electrode substrate or the concentration of the metal salt and phosphorus source, the thickness of the coating layer on the surface of the positive electrode material can be conveniently regulated, thereby significantly improving the cycle stability and rate performance of the positive electrode material without losing the battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a transmission electron microscope photograph of the aluminum phosphate-coated ternary single crystal nickel cobalt lithium manganese oxide particles of Example 1.

[0054] Figure 2This is a transmission electron microscope photograph of the aluminum phosphate-coated single-crystalline lithium cobalt oxide particles of Example 2.

[0055] Figure 3 This is a low-magnification transmission electron microscope photograph of the aluminum phosphate-coated high-pressure lithium nickel manganese oxide particles of Example 3.

[0056] Figure 4 This is a transmission electron microscope photograph of the 20nm aluminum phosphate-coated high-pressure lithium nickel manganese oxide particles of Example 3 at a magnified multiple.

[0057] Figure 5 This is an X-ray energy dispersive spectroscopy (EDS) image of the 20 nm aluminum phosphate-coated high-pressure lithium nickel manganese oxide particles of Example 3.

[0058] Figure 6 This is a transmission electron microscope photograph of the 4nm aluminum phosphate-coated high-pressure lithium nickel manganese oxide particles of Example 4.

[0059] Figure 7 This is a transmission electron microscope photograph of the 9nm aluminum phosphate-coated high-pressure lithium nickel manganese oxide particles of Example 5.

[0060] Figure 8 The cycle performance of the positive electrode materials corresponding to Example 5 and Comparative Examples 1-2 at a charge and discharge current of 140 mA / g. DETAILED DESCRIPTION

[0061] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0062] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0063] The present invention is further described below using aluminum phosphate as an example, and other metal phosphate coating methods are similar. According to the specific reaction system, the corresponding metal salt, anti-solvent, and coating substrate are selected, and the interaction between the precursor mixture and the anti-solvent is controlled by an appropriate feeding method to achieve the deposition of different metal phosphates on the substrate surface. The thickness of the surface coating layer is conveniently regulated by changing the concentration of the metal salt and the phosphorus source, the amount of the coating substrate, the feeding method, etc., and finally the surface phosphorus-containing metal salt is modified to the interface of the positive electrode material by calcination. However, the present invention is not limited to the following embodiments. The methods are conventional methods unless otherwise specified. The raw materials can be obtained from public commercial channels unless otherwise specified.

[0064] Example 1

[0065] Preparation of aluminum phosphate-modified ternary single-crystal nickel-cobalt-manganese oxide particles with core-shell structure

[0066] 1) Dissolve 0.067 g of aluminum sulfate 18hydrate and 0.012 g of ammonium dihydrogen phosphate in 15 ml of deionized water, stir and dissolve continuously and react for 12 hours to form a mixed solution;

[0067] 2) dispersing 0.98 g of ternary single crystal nickel cobalt lithium manganese oxide powder in the mixed solution formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;

[0068] 3) Slowly adding 45 ml of anhydrous ethanol into the turbid solution formed in step 2) and stirring the solution continuously, centrifuging, washing and drying to obtain a base powder uniformly coated with metal aluminum phosphorus species;

[0069] 4) The base powder formed in step 3) is calcined at 700° C. for 2 h to obtain a nickel cobalt manganese oxide material modified with aluminum phosphate.

[0070] The ternary single crystal nickel cobalt manganese oxide particles modified by aluminum phosphate are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 1 As shown in the figure, the average size of the substrate lithium nickel cobalt manganese oxide single crystal particles is about 3 μm, the surface shell thickness is 28 nm, and aluminum phosphate is continuously and evenly distributed on the surface of the ternary positive electrode substrate.

[0071] Example 2

[0072] Preparation of single-crystalline lithium cobalt oxide particles modified with aluminum phosphate with core-shell structure

[0073] 1) Dissolve 0.134 g of aluminum sulfate 18hydrate and 0.024 g of ammonium dihydrogen phosphate in 15 ml of deionized water, stir and dissolve continuously and react for 12 hours to form a mixed solution;

[0074] 2) dispersing 0.98 g of single crystal lithium cobalt oxide powder in the mixed solution formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;

[0075] 3) Slowly adding 45 ml of anhydrous ethanol into the turbid solution formed in step 2) and stirring the solution continuously, centrifuging, washing and drying to obtain a base powder uniformly coated with metal aluminum phosphorus species;

[0076] 4) The base powder formed in step 3) is calcined at 700° C. for 2 h to obtain a lithium cobalt oxide material modified with aluminum phosphate.

[0077] The ternary single crystal lithium cobalt oxide particles modified by aluminum phosphate are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 2As shown in the figure, the average size of the substrate lithium cobalt oxide single crystal particles is about 8 μm, the surface shell thickness is 60 nm, and aluminum phosphate is continuously and evenly distributed on the surface of the lithium cobalt oxide positive electrode substrate.

[0078] Example 3

[0079] Preparation of aluminum phosphate-modified high-pressure lithium nickel manganese oxide particles with core-shell structure

[0080] 1) Dissolve 0.067 g of aluminum sulfate 18hydrate and 0.012 g of ammonium dihydrogen phosphate in 15 ml of deionized water, stir and dissolve continuously and react for 12 hours to form a mixed solution;

[0081] 2) dispersing 1.83 g of spinel nickel lithium manganese oxide powder in the mixed solution formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;

[0082] 3) Slowly adding 45 ml of anhydrous ethanol into the turbid solution formed in step 2) and stirring the solution continuously, centrifuging, washing and drying to obtain a base powder uniformly coated with metal aluminum phosphorus species;

[0083] 4) The base powder formed in step 3) is calcined at 700° C. for 2 h to obtain a lithium nickel manganese oxide material modified with aluminum phosphate.

[0084] The spinel nickel manganese oxide particles modified by aluminum phosphate are typical core-shell structures, as shown in the transmission electron microscope image. Figure 3 The average size of the substrate lithium nickel manganese oxide particles is about 1-10 μm, and the magnified transmission electron microscope image is shown in Figure 4 As shown, the surface shell thickness is 20nm, and the X-ray energy dispersive spectrometry (EDS) image ( Figure 5 ) shows that phosphorus and aluminum are continuously and evenly distributed on the surface of the lithium nickel manganese oxide positive electrode substrate.

[0085] Example 4

[0086] Preparation of high-voltage lithium nickel manganese oxide particles with a 4 nm aluminum phosphate coating

[0087] 1) Dissolve 0.134 g of aluminum sulfate 18hydrate and 0.024 g of ammonium dihydrogen phosphate in 15 ml of deionized water, stir and dissolve continuously and react for 12 hours to form a mixed solution;

[0088] 2) dispersing 7.30 g of spinel nickel lithium manganese oxide powder in the mixed solution formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;

[0089] 3) Slowly adding 45 ml of anhydrous ethanol into the turbid solution formed in step 2) and stirring the solution continuously, centrifuging, washing and drying to obtain a base powder uniformly coated with metal aluminum phosphorus species;

[0090] 4) The base powder formed in step 3) is calcined at 700° C. for 2 h to obtain a lithium nickel manganese oxide material modified with aluminum phosphate.

[0091] The spinel nickel manganese oxide particles modified by aluminum phosphate are typical core-shell structures, as shown in the transmission electron microscope image. Figure 6 As shown, the average size of the base lithium nickel manganese oxide particles is about 1-10 μm, the surface shell thickness is 4 nm, and aluminum phosphate is continuously and evenly distributed on the surface of the lithium nickel manganese oxide positive electrode base.

[0092] Example 5

[0093] 1. Preparation of high-voltage lithium nickel manganese oxide particles with a 9nm aluminum phosphate coating

[0094] 1) Dissolve 0.134 g of aluminum sulfate 18hydrate and 0.024 g of ammonium dihydrogen phosphate in 15 ml of deionized water, stir and dissolve continuously and react for 12 hours to form a mixed solution;

[0095] 2) dispersing 3.65 g of spinel nickel lithium manganese oxide powder in the mixed solution formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;

[0096] 3) Slowly adding 45 ml of anhydrous ethanol into the turbid solution formed in step 2) and stirring the solution continuously, centrifuging, washing and drying to obtain a base powder uniformly coated with metal aluminum phosphorus species;

[0097] 4) The base powder formed in step 3) is calcined at 700° C. for 2 h to obtain a lithium nickel manganese oxide material modified with aluminum phosphate.

[0098] The spinel nickel manganese oxide particles modified by aluminum phosphate are typical core-shell structures, as shown in the transmission electron microscope image. Figure 7 As shown. The average size of the base lithium nickel manganese oxide particles is about 1-10μm, the surface shell thickness is 9nm, and aluminum phosphate is continuously and evenly distributed on the surface of the lithium nickel manganese oxide positive electrode substrate. By conveniently changing the content of the coating substrate, the controllable coating of aluminum phosphate of different thicknesses on the surface of the lithium nickel manganese oxide substrate can be directly achieved, and the regulation match between the synthesis conditions and the coating layer thickness can be established.

[0099] 2. Preparation of aluminum phosphate modified lithium nickel manganese oxide electrode

[0100] 0.24 g of the modified lithium nickel cobalt manganese oxide positive electrode powder in the above Example 5 was mixed with 0.03 g of acetylene black as a conductive additive, 0.6 g of 5% mass concentration of PVDF as a binder, and a small amount of solvent NMP. After slurrying, coating (aluminum sheet as current collector), and drying, an aluminum phosphate-modified lithium nickel manganese oxide electrode sheet was obtained.

[0101] 3. Assemble the battery

[0102] The prepared aluminum phosphate-modified lithium nickel manganese oxide electrode was used as the positive electrode, lithium metal was used as the negative electrode, a polypropylene microporous membrane (Celgard 2400) was used as the separator, and 1 mol / L LiPF6 was used as the electrolyte to assemble a button cell in an argon-protected glove box.

[0103] 4. Battery Test

[0104] The battery was subjected to constant current charge and discharge tests using a charge and discharge instrument, with a test voltage range of 3 to 5 V and a test temperature of 25° C. The battery specific capacity and charge and discharge current were calculated based on the mass of lithium nickel manganese oxide.

[0105] Comparative Example 1

[0106] 1. Take the uncoated positive electrode material to prepare an uncoated lithium nickel manganese oxide electrode, and the specific steps are the same as step 2 in Example 5.

[0107] 3. Assemble the battery. The specific steps are the same as step 3 in Example 5.

[0108] 4. Battery test: the specific steps are the same as step 4 in embodiment 5.

[0109] Comparative Example 2

[0110] 1. Preparation of lithium nickel manganese oxide positive electrode material partially coated with aluminum phosphate

[0111] 1) Dissolve 0.134 g of aluminum sulfate 18hydrate and 0.024 g of ammonium dihydrogen phosphate in 15 ml of deionized water, stir and dissolve continuously and react for 12 hours to form a mixed solution;

[0112] 2) dispersing 3.65 g of spinel nickel lithium manganese oxide powder in the mixed solution formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution, and centrifuging, washing, and drying the turbid solution to obtain a base powder partially coated with aluminum phosphate;

[0113] 3) The base powder formed in step 2) is calcined at 700° C. for 2 h to obtain a lithium nickel manganese oxide positive electrode material partially coated with aluminum phosphate.

[0114] 2. Prepare a partially coated lithium nickel manganese oxide material electrode, the specific steps are the same as step 2 in Example 5.

[0115] 3. Assemble the battery. The specific steps are the same as step 3 in Example 5.

[0116] 4. Battery test: the specific steps are the same as step 4 in embodiment 5.

[0117] Figure 8The cycle performance of the positive electrode materials corresponding to Example 5 and Comparative Examples 1 and 2 at a charge and discharge current of 1C (140mA / g). After nearly 400 cycles, the discharge capacity of the sample in Example 5 was 121mAh / g, showing a capacity retention rate of up to 98%, which was significantly higher than 60mAh / g (capacity retention rate 52%) of the uncoated sample and 103mAh / g (capacity retention rate 84%) of the partially coated sample, which significantly improved the cycle stability and life of the battery, reflecting the outstanding significance of a uniform and controllable interface modification structure for stabilizing the battery interface and achieving long cycle performance.

[0118] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a phosphate-modified positive electrode material, the preparation method comprising: 1) dissolving a metal salt and a phosphorus source in deionized water, reacting to form a mixed solution; 2) dispersing the coated substrate material in the mixed solution formed in step 1) to obtain a turbid solution; 3) stirring the anti-solvent and the turbid solution formed in step 2) to react, centrifuging, washing, and drying to obtain a base powder coated with a metal phosphorus-containing species; 4) The base powder formed in step 3) is calcined to obtain a phosphate-modified positive electrode material.

2. The preparation method according to claim 1, characterized in that: The metal salt is selected from one or more of chlorides, sulfates, nitrates, acetates and alkoxides of metal elements. Preferably, the metal element is selected from at least one of aluminum, nickel, manganese, cobalt, iron, copper, zinc, titanium, zirconium, niobium, tantalum and magnesium. Preferably, in the mixed solution of step 1), the concentration of the metal salt is 0.001 to 1 mol / L. Preferably, the phosphorus source is selected from one or more of the corresponding ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, and potassium phosphate. Preferably, in the mixed solution of step 1), the concentration of the phosphorus source is 0.001-1 mol / L. Preferably, in the mixed solution of step 1), the reaction conditions for forming the mixed solution include: the reaction temperature is room temperature to 60° C.; and the reaction time is 1 h to 72 h. Preferably, in the mixed solution of step 1), the molar ratio of the metal salt to the phosphorus source is 0.001-1:0.001-1.

3. The preparation method according to claim 1 or 2, characterized in that: The coating substrate material is selected from at least one of metal materials, non-metal materials, oxides, sulfides, carbides, nitrides, phosphides, lithium salt positive electrode materials, sodium salt positive electrode materials, potassium salt positive electrode materials, and organic particles. Preferably, the metal in the coating substrate material is selected from at least one of gold, silver, ruthenium, rhodium, palladium, platinum, germanium, tin, antimony and alloys thereof. Preferably, the non-metal in the coating substrate material is selected from at least one of carbon, silicon, sulfur, phosphorus and selenium. Preferably, the oxide in the coating substrate material is selected from at least one of silicon dioxide, titanium dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium oxide, manganese dioxide, manganese tetraoxide, iron oxide, iron oxide, cobalt oxide, nickel oxide, vanadium pentoxide, zirconium oxide, molybdenum oxide, indium tin oxide, tin oxide, and lithium lanthanum zirconium oxide. Preferably, the sulfide in the coating substrate material is selected from at least one of zinc sulfide, tungsten sulfide, bismuth sulfide, titanium disulfide, iron sulfide, cobalt sulfide, nickel sulfide, molybdenum sulfide, tin sulfide and antimony sulfide. Preferably, the carbide in the coating substrate material is selected from at least one of silicon carbide, titanium carbide, calcium carbide, vanadium carbide, chromium carbide, tantalum carbide, tungsten carbide and boron carbide. Preferably, the nitride in the coating substrate material is selected from at least one of boron nitride, gallium nitride, silicon nitride, titanium nitride, vanadium nitride, niobium nitride, tungsten nitride and phosphorus nitride. Preferably, the phosphide in the coating substrate material is selected from at least one of iron phosphide, cobalt phosphide, nickel phosphide, titanium phosphide, molybdenum phosphide and tin phosphide. Preferably, the lithium salt positive electrode material in the coating substrate material includes but is not limited to at least one of lithium titanate, lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium-rich nickel cobalt manganese oxide, lithium titanium phosphate, lithium titanium aluminum phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and lithium manganese cobalt phosphate. Preferably, the sodium salt positive electrode material in the coating substrate material is selected from at least one of oxide sodium salt positive electrode materials, polyanion sodium salt positive electrode materials, Prussian blue sodium salt positive electrode materials, fluoride sodium salt positive electrode materials, and organic compound sodium salt positive electrode materials. Preferably, the potassium salt positive electrode material in the coating substrate material is selected from at least one of Prussian blue-based potassium salt positive electrode materials, layered oxide-based potassium salt positive electrode materials, polyanion-based potassium salt positive electrode materials, and organic material-based potassium salt positive electrode materials. Preferably, the organic particles in the coating substrate material are selected from at least one of phenolic resin, urea-formaldehyde resin, melamine resin, polystyrene, polydopamine and polyvinyl pyrrolidone.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the turbid solution of step 2), the concentration of the coated substrate is 0.001-1000 g / L. Preferably, the anti-solvent includes but is not limited to at least one of methanol, ethanol, propanol, butanol, pentanol, hexanol, acetone, butanone, furfural, acetonitrile and dioxane. Preferably, in step 3), the volume ratio of the turbid liquid to the anti-solvent is 1-30:30-100.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The method of mixing the turbid liquid with the antisolvent includes: directly pouring the turbid liquid, slowly dripping it, and controlling the dripping rate by a peristaltic pump to drip into the antisolvent; or directly pouring the antisolvent, slowly dripping it, and controlling the dripping rate by a peristaltic pump to drip into the turbid liquid. Preferably, the temperature at which the turbid solution and the anti-solvent are stirred is room temperature to 80°C. Preferably, the turbid liquid and the anti-solvent are stirred at a rotation speed between 100 r / min and 1000 r / min. Preferably, the stirring reaction time is 5 to 240 minutes.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The calcination atmosphere is at least one of oxygen, air, nitrogen and argon. Preferably, the calcination conditions include: a calcination temperature of 300 to 900° C. and a calcination time of 1 to 10 hours.

7. A phosphate-modified positive electrode material, wherein the phosphate-modified positive electrode material is prepared by the preparation method according to any one of claims 1 to 7.

8. The positive electrode material according to claim 7, characterized in that The phosphate-modified positive electrode material is a particle with a core-shell structure. Preferably, the phosphate-modified positive electrode material comprises a nano-coating shell layer and a coating substrate material, wherein the nano-coating shell layer is modified on the surface of the coating substrate material; and the nano-coating shell layer comprises phosphate. Preferably, the nano-coating shell layer partially or completely coats the surface of the coating substrate material. Further, the nano-coating shell layer is continuously and evenly distributed on the surface of the coating substrate material.

9. The positive electrode material according to claim 7 or 8, characterized in that: The nano-coating shell layer includes phosphate of the metal element. Preferably, the thickness of the nano-coating shell layer is 0 nm to 500 nm.

10. Use of the coated positive electrode material according to any one of claims 7 to 9 in energy storage batteries.

Citation Information

Patent Citations

  • Preparation method of lithium phosphate coated lithium-ion battery ternary positive electrode material

    CN110190254A

  • A coated modified cathode material, its preparation method, and a lithium-ion battery

    CN111916702B

  • Positive electrode active material coating liquid and preparation method therefor and positive electrode active material coating method

    CN106960958A

  • Production method of Na<3>V<2>(PO<4>)<3>-based quasi-symmetric high-voltage sodium ion secondary battery

    CN107123809A

  • Silicon-based negative electrode material, preparation method thereof and application of silicon-based negative electrode material in lithium ion battery

    CN113594455A

Cited By

  • Organic metal framework coated lithium cobalt oxide positive electrode material and preparation method and application thereof

    CN120784314A

  • A lithium cobalt oxide cathode material coated with an organic metal framework and a preparation method and application thereof

    CN120784314B